Technical evaluation of a novel combined cooling-heating-power-water system based on PEM fuel cells - Kai Kang; Yunlong Zhang; Chuansheng Cao; Xinyu Lu (Energy Conversion and Management: X)
The low temperature of the recovered waste heat is the main constraint on the performance of the cogeneration system based on PEM fuel cell (PEMFC). Therefore, this study proposes a novel PEMFC combined cooling-heating-power-water system. The proposed system consists of a PEMFC, a solar thermal collector (STC), a LiBr adsorption chiller (AC), a multi-effect desalination (MED) process, etc. The STC secondary heating stack cooling water allows the system to use a Libr AC with a higher COP for cooling output, realizing that the cooling/heating outputs of the system are independent of each other. The cooling output only affects the output power, and the heating output only affects the fresh water production. The energy and exergy analysis demonstrate the proposed system can follow the variation of typical electrical/heating/cooling loads in time. In 24 h of operation, the proposed system consumes 19.53 kg of hydrogen and produces 4,355 kg of fresh water. The energy efficiency and exergy efficiency of the system are 78.5 % and 53.8 %, respectively. Furthermore, if the application scenario has higher solar radiation, the cooling output time of the LiBr AC can be extended, to reduce the hydrogen consumption.